Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1159/000228644
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia Susceptibility in Mice after Therapy with β-Catenin-Transduced Hematopoietic Progenitor Cells after Myocardial Ischemia/Reperfusion

Abstract: Background: Hematopoietic progenitor cells (HPCs) can improve cardiac function after myocardial infarction. However, occurrence of arrhythmias is a potential limitation of cell therapy. In this study, we investigated the cardiac electrophysiological properties of ex vivo expanded HPCs, generated by β-catenin gene transfer, after transcoronary delivery in a murine model of ischemia/reperfusion (I/R) injury. Methods and Results: To assess arrhythmia inducibility of ex vivo expanded HPCs, mice were subjected to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Some of the common IR-related abnormal changes in the ECG include R-wave enlargement, development of Q-waves, and ST-segment elevation. This model has proven useful in the assessment of the efficacy of antiarrhythmic and anti-ischemic drugs (Burger et al, 2009;Dhalla et al, 2009;Gardiwal et al, 2009;Gandhi et al, 2009;Wajima et al, 2004;Wehrens et al, 2000). IR has also been used as a challenge procedure to determine if toxicant treatment can modify responses to myocardial injury.…”
Section: Ischemia-reperfusionmentioning
confidence: 99%
“…Some of the common IR-related abnormal changes in the ECG include R-wave enlargement, development of Q-waves, and ST-segment elevation. This model has proven useful in the assessment of the efficacy of antiarrhythmic and anti-ischemic drugs (Burger et al, 2009;Dhalla et al, 2009;Gardiwal et al, 2009;Gandhi et al, 2009;Wajima et al, 2004;Wehrens et al, 2000). IR has also been used as a challenge procedure to determine if toxicant treatment can modify responses to myocardial injury.…”
Section: Ischemia-reperfusionmentioning
confidence: 99%
“…In this context, it was demonstrated that β-catenin modification of HSCs can significantly improve cardiac function in mice models of ischemia-reperfusion without changing electrophysiological properties of cardiomyocytes. 27,28 Unfortunately, subsequent clinical trials using HSCs had the same negative outcome. Both intracoronary 66 and intramyocardial 67 autologous transplantation of HSCs did not improve cardiac performance and the latter even showed an increased frequency and severity in adverse events.…”
Section: Hematopoietic Stem Cells (Hscs)mentioning
confidence: 99%
“…Researchers tried to improve HSC therapeutic efficiency by genetic transduction. In this context, it was demonstrated that β‐catenin modification of HSCs can significantly improve cardiac function in mice models of ischemia‐reperfusion without changing electrophysiological properties of cardiomyocytes 27,28 . Unfortunately, subsequent clinical trials using HSCs had the same negative outcome.…”
Section: Stem Cell Types For Myocardial Repairmentioning
confidence: 99%